Morphological and molecular identification for two new species of wood-inhabiting macrofungi (Basidiomycota) from Yunnan-Guizhou Plateau, China - Yang, Yang; Li, Rong; Liu, Chaomao; Zhao, Changlin (Phytotaxa, 2023)
Two new wood-inhabiting macrofungal species, Coniophora yunnanensis and Resupinatus yunnanensis are proposed based on a combination of morphological features and molecular evidence. Coniophora yunnanensis is characterized by annual basidiomata with odontoid hymenophore with olivaceous to brown hymenial surfaces, a monomitic hyphal system with simple septate generative hyphae, and yellowish basidiospores. While, R. yunnanensis is characterized by resupinate to cupulate basidiomata with greyish to greyish-brown hymenophore, a monomitic hyphal system with clamped generative hyphae and ellipsoid basidiospores measuring as 4.5–9 × 3.5–7 µm. The phylogenetic analyses based on molecular data of ITS+nLSU sequences showed that C. yunnanensis and R. yunnanensis nested within Agaricomycetidae, in which C. yunnanensis clustered into the family Coniophoraceae (Boletales), and R. yunnanensis grouped into family Pleurotaceae (Agaricales). The phylogenetic tree derived from ITS sequences revealed that C. yunnanensis grouped into genus Coniophora, in which it grouped with C. marmorata. Additionally, R. yunnanensis clustered into genus Resupinatus and then was sister to R. conspersus.